Genetic diversity of gamma ray aplication result on Mandarin’s SoE using ISSR markers - Putri Kendari; Mahfut Mahfut (Tropical Genetics, 2021)
Mandarin’s SoEare one of Indonesia's leading mandarinto substitute imported oranges. The quality of oranges can be improved through breeding programs, one of which is mutation breeding using gamma rays. The purpose of this study was to obtain information about the genetic variation of SoE mandarin resulting from gamma ray radiation using ISSR markers. PCR results with ISSR markers on tangerine plants produced by gamma ray radiation showed various patterns, namely the bands were the same, lost bands, and experienced the addition of new bands compared to control plants.